2019
DOI: 10.1021/acs.joc.9b00209
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid-Promoted Regio- and Diastereoselective Cross-Coupling of Aryl-Substituted 1,2-Diols and Boronic Acids

Abstract: A Lewis acid-promoted highly regio- and diastereoselective C­(sp3)–C­(sp2) cross-coupling reaction between unprotected aryl-substituted 1,2-diols and styryl-, aryl-, heteroaryl-, and polyarylboronic acids has been developed in a one-pot procedure. The regioselective opening of aryl-substituted cyclic boronic esters promoted by a Lewis acid followed by subsequent intramolecular 1,4-transfer of the carbon ligand from boron to a resonance-stabilized benzylic carbenium ion minimizing the allylic 1,3-strain in a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The HMBC correlations from H–OH 13 (δ H 5.87, s) to C-12/C-13/C-14 further confirmed that the monoterpene moiety was linked to C-12. The NOESY correlations (Figure ) of H-30/H-28 and the coupling constant of 6.4 H Z between H-28 and H-29 indicated the relative trans -configuration of C-28 and C-29 in 1 . Thus, the structure of 1 was established and named myrifratin A ( 1 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The HMBC correlations from H–OH 13 (δ H 5.87, s) to C-12/C-13/C-14 further confirmed that the monoterpene moiety was linked to C-12. The NOESY correlations (Figure ) of H-30/H-28 and the coupling constant of 6.4 H Z between H-28 and H-29 indicated the relative trans -configuration of C-28 and C-29 in 1 . Thus, the structure of 1 was established and named myrifratin A ( 1 ).…”
Section: Resultsmentioning
confidence: 96%
“…The NOESY correlations (Figure 2) of H-30/H-28 and the coupling constant of 6.4 H Z between H-28 and H-29 indicated the relative trans-configuration of C-28 and C-29 in 1. 22 Thus, the structure of 1 was established and named myrifratin A (1).…”
Section: Journal Of Agricultural and Foodmentioning
confidence: 99%
“…Despite the lack of previous records on the biosynthesis of cherylline, it has received much attention with regard to synthetic chemistry aspects and natural product isolation, even until today. 40–42…”
Section: Structural Diversity and Biogenesis Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%
“…Despite the lack of previous records on the biosynthesis of cherylline, it has received much attention with regard to synthetic chemistry aspects and natural product isolation, even until today. [40][41][42] Few studies regarding cherylline have been published since 2017. Shi et al (2018) examined the one-pot synthesis of two constitutional isomers: (±)-latine and (±)-cherylline.…”
Section: Cherylline Typementioning
confidence: 99%